2016
DOI: 10.1111/imm.12678
|View full text |Cite
|
Sign up to set email alerts
|

Fungal pattern receptors down‐regulate the inflammatory response by a cross‐inhibitory mechanism independent of interleukin‐10 production

Abstract: Cyclic AMP regulatory element binding protein and signal transducer and activator of transcription 3 (STAT3) may control inflammation by several mechanisms, one of the best characterized is the induction of the expression of the anti-inflammatory cytokine interleukin-10 (IL-10). STAT3 also down-regulates the production of pro-inflammatory cytokines induced by immunoreceptor tyrosine-based activation motif (ITAM)-coupled receptors, a mechanism termed cross-inhibition. Because signalling via ITAM-dependent mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…A recently report has shown that IL-10 production in human monocyte-derived DCs was increased by zymosan stimulus, which induced STAT3 Tyr705 phosphorylation. It was also observed that when cells were stimulated in the presence of WEB2086, STAT3 Tyr705 phosphorylation was reduced [42]. These data reinforce our findings in associating PAFR/STAT3 activation in IL-10 production in DCs.…”
Section: Discussionsupporting
confidence: 90%
“…A recently report has shown that IL-10 production in human monocyte-derived DCs was increased by zymosan stimulus, which induced STAT3 Tyr705 phosphorylation. It was also observed that when cells were stimulated in the presence of WEB2086, STAT3 Tyr705 phosphorylation was reduced [42]. These data reinforce our findings in associating PAFR/STAT3 activation in IL-10 production in DCs.…”
Section: Discussionsupporting
confidence: 90%
“…This explains a positive feedback loop between HIF1 and STAT3 since Y705-STAT3 activates HIF1α transcription ( 36 , 37 ). In a previous study, we observed that both zymosan and LPS are robust activators of Y705-STAT3 phosphorylation through the induction of secondary mediators ( 38 ). In keeping with that report, the assay of P-Y705-STAT3 in nuclear extracts showed a time-course compatible with its involvement in HIF1α expression (Figure 2 A).…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, yeast-derived β-glucans induce DC maturation, significantly increase tumor-specific cytotoxic T lymphocyte (CTL) responses [53] and program DC to express cell adhesion and migration mediators, antimicrobial molecules, and Th17-polarizing factors [54]. Furthermore, the role of secondary mediators, which include lipids, in the induction of the cytokine signature was demonstrated in DC stimulated with zymosan, a cell-wall extract from Saccharomyces cerevisiae that contains a β-glucan component, providing mechanistic clues that β-glucans can modulate the immune response by acting on the lipid mediator cascade and by activating STAT3 signaling [55,56]. The regulation of additional cellular responses by mushroom-derived β-glucans in monocytes and DC has been also described.…”
Section: In Vitro Effects On Innate Immunity Cellsmentioning
confidence: 99%